Paciente masculino de 26 horas de nacido con sepsis temprana. - Ramírez Acosta, Miguel Angel (2018)
Neonatal sepsis is a major cause of death in critically ill patients. It should be mentioned that there is a greater generation of knowledge in the understanding of what happens in newborns with early neonatal sepsis, this due to the understanding of the concept of fetal inflammatory response syndrome. The adequate application of the different concepts in neonatal sepsis; the establishment of management protocols based on local epidemiology and; Having knowledge of the resistance profile of the germs will have as impact a better quality in the neonatal care, a rational and adequate use of the different medicines (among them the antibiotics), an improvement in the morbidity and mortality and a smaller impact in the generation of bacterial resistance. Every day there are novel concepts about neonatal sepsis, which must be known and incorporated, if they merit, into medical practice to generate higher quality care.